2008
DOI: 10.1002/casp.948
|View full text |Cite
|
Sign up to set email alerts
|

Protection, manipulation or interference with relationships? Discourse analysis of New Zealand lawyers' talk about supervised access and partner violence

Abstract: Violence against women within the context of intimate relationships is a complex social problem in Aotearoa/New Zealand and internationally. Such abuse by men is particularly problematic because of its prevalence, and because of the extent and magnitude of deleterious effects on the health and psychological well-being of women and children. In New Zealand, the legal system is assumed to play an important role in protecting women and children from domestic violence. Through the Domestic Violence Act 1995 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
1
12
0
2
Order By: Relevance
“…This is in line with arguments made by Conner (2009), who identified that judges held a belief that women had a tendency to exaggerate DV. Furthermore, the positioning of mothers as alleging DV as a means to manipulate the system concurs with previous findings; Pond and Morgan (2008) found that some lawyers’ discourses questioned mothers’ integrity and their motivations in obtaining protection orders. However, it is in direct contrast with the known cost of DV to women and children in Irish society.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in line with arguments made by Conner (2009), who identified that judges held a belief that women had a tendency to exaggerate DV. Furthermore, the positioning of mothers as alleging DV as a means to manipulate the system concurs with previous findings; Pond and Morgan (2008) found that some lawyers’ discourses questioned mothers’ integrity and their motivations in obtaining protection orders. However, it is in direct contrast with the known cost of DV to women and children in Irish society.…”
Section: Discussionsupporting
confidence: 88%
“…A few examples in this area do exist nonetheless. Pond and Morgan (2008) undertook a DA of interviews with lawyers, where they identified discourses which portrayed the need to protect children via supervised access. However, they also identified discourses which portrayed mothers who alleged DV as both obstructive and ‘misusing the system’ to their own gain.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms allow lawyers to not only highlight, silence or contest aspects of the identity of characters in their narratives, but also to position them in relation to each other by portraying them as exercising (or lacking in) agency, power and control over another actor, thereby indicating responsibility (or lack thereof) for such acts. For example, Pond and Morgan (2008) find that defence lawyers use the ‘violent partner’ but ‘good father’ description to negotiate the identity of clients who have committed domestic violence but who are also seeking child custody. As a result, these men are portrayed as perfectly safe around children despite being violent towards their partners.…”
Section: Introductionmentioning
confidence: 99%
“…Para as pesquisadoras, esta realidade torna provável que mulheres vítimas de violência doméstica tornem-se apreensivas em utilizar o sistema legal na busca de proteção de seus filhos. Isso porque há a possibilidade de a manutenção do convívio paterno-filial ser privilegiada, em detrimento da segurança das crianças, por meio de procedimentos como a mudança prematura do contato supervisionado para sem supervisão (Pond & Morgan, 2008).…”
Section: -Visitas Monitoradas E Violência Domésticaunclassified
“…Por fim, as pesquisadoras alertam que, caso tais discursos se tornem abundantes nos círculos judiciais, isto poderá prejudicar o sucesso das medidas de proteção e dos pedidos por contato supervisionado. Comprometer-se-á, deste modo, a segurança de mulheres e crianças inseridas em um contexto de violência doméstica (Pond & Morgan, 2008). Na Austrália, Sheehan et al (2007) igualmente informam que mudanças na lei daquele país marcaram ".…”
Section: -Visitas Monitoradas E Violência Domésticaunclassified